Medical Tourism in Malaysia: Growth, Contributions and Challenges - Narayanan, Suresh; Lai, Yew Wah (Thailand and The World Economy, 2021)
Medical tourism in Malaysia has seen phenomenal growth since 2002, emerging as an additional engine of growth, particularly after the financial crisis of 2008. The active involvement of private sector healthcare providers, aided by friendly government policies, and the indirect participation of the government through government-linked healthcare companies have spearheaded tremendous changes in the industry. Along with the promise of increased direct employment, opportunities in related sectors, both directly and indirectly, and economic growth, this unprecedented growth also brings challenges in the short and longer-terms. We provide an update focusing, in particular, on the industry’s contributions, the controversies that have arisen and the likely challenges it would face in the coming years.